Spin‐modulated spacecraft floating potential: Observations and effects on electron moments. Issue 2 (3rd February 2014) - Pulupa, M. P.; Bale, S. D.; Salem, C.; Horaites, K.
Abstract Using the Three‐Dimensional Plasma electron analyzers on the Wind spacecraft, we have analyzed several years of solar wind electron data. We find an anomalous core electron drift of roughly 40 km/s in the sunward xGSEdirection, regardless of the direction of the magnetic field. We interpret this drift as an effect of a spin modulation in the spacecraft floating potential, which can be effectively modeled with the addition of a dipole term to the potential. For typical solar wind conditions, the amplitude of potential modulation is a fraction of a volt. The modulation has negligible effects on the even electron moments (density and temperature) but noticeable effects on the odd moments (bulk velocity and heat flux).